(Trans)regional embeddedness and the resilience of offshore campuses. Issue 1 (31st December 2023) - Kleibert, Jana M.; Schulze, Marc P.; Rottleb, Tim; Bobée, Alice
ABSTRACT: Regional embeddedness plays an important role for universities. We show that for transnational subsidiaries of universities, or offshore campuses, which are necessarily transregionally embedded through their relations to their home university campus and its networks, the level of regional embeddedness is also of critical importance. We define four dimensions of regional and transregional embeddedness: partnerships, government funding, faculty and staff, and student recruitment. Based on qualitative interviews conducted before and at the onset of the COVID-19 pandemic and a global survey of offshore campus managers during the pandemic, we show how campuses with strong regional embeddedness seem to have been more resilient in the face of the COVID-19 crisis than those campuses which are less strongly regionally embedded. Nonetheless, regional embeddedness of institutions is no panacea and its risks and trade-offs with transregional embeddedness should be carefully weighed by higher education managers.